2016
DOI: 10.3390/en9060455
|View full text |Cite
|
Sign up to set email alerts
|

A Stackelberg Game Theoretic Analysis of Incentive Effects under Perceived Risk for China’s Straw-Based Power Plant Supply Chain

Abstract: Abstract:The rapid expansion of the biomass power generation industry has resulted in the conversion of substantial agricultural waste (crop straw) into energy feedstock, thereby increasing the income of farmers and promoting the development of rural areas. However, the promising industry faces financial deficits because of difficulties in collecting straw from farmers. To determine strategies for overcoming the biomass supply problem, we apply Stackelberg game theory in modeling the Chinese biomass supply cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The unit transportation cost and the transportation distance do not have significant impacts on the stable percentage. It is important to note that as the benefit sharing ratio increases, fewer farmers are willing to participate in the VC method when non-monetary utility is not included into the farmer agents' payoff function as shown in Equation (5). This scenario represents the situation where farmers only care about monetary returns and the benefit sharing policy is not applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit transportation cost and the transportation distance do not have significant impacts on the stable percentage. It is important to note that as the benefit sharing ratio increases, fewer farmers are willing to participate in the VC method when non-monetary utility is not included into the farmer agents' payoff function as shown in Equation (5). This scenario represents the situation where farmers only care about monetary returns and the benefit sharing policy is not applied.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on agricultural biomass-straw-because the distribution of forest biomass is more centralized and its production and supply system is better-developed than straw. As a major agricultural producer, China has the potential to produce a large amount of agriculture straw [5]. The theoretical annual production of agricultural biomass resources is approximately 870 million t (440 million tce), and approximately 400 million t (200 million tce) are available as energy sources [6], including wheat, corn, and rice straw.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that each SPP collects straw within a radius of 30 km, and 65 SPPs are required to completely cover the study area under ideal circumstances. Because it is difficult to reasonably determine N in advance, N was set to 5,10,15,20,25,30,35,40,45,50,55,60, and 65 for experimentation. Moreover, the straw-based electricity price also affects the economic revenue generated by running SPPs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, another study's results showed a clear difference in the effectiveness of incentives for various actors. Providing incentives to farmers can increase the profits earned by all stakeholders in biomass power generation [51].…”
Section: Central Government Levelmentioning
confidence: 99%